Prehistoric human activity and its environmental background in Lake Donggi Cona basin, northeastern Tibetan Plateau. (May 2020) - Gao, Jingyi; Hou, Guangliang; Wei, Haicheng; Chen, Youcheng; E, Chongyi; Chen, Xiaoliang; Lancuo, Zhuoma
Lake Donggi Cona is a key area for the exploration of the prehistoric settlement of the inner Tibetan Plateau because of its location in the joint of the higher inner Tibetan Plateau and the upper Yellow River valley. Here, we carried out archeological investigation on the lake basin, and a total of 256 pieces of stone artifacts were collected from the surface of the DJCN 3-2-2 site on the northern shore terraces of the lake. In addition, AMS 14 C and OSL dating were performed on hearths and section (DJCN 3-2-2), respectively; meanwhile environmental proxies, including grain size, charcoal, magnetic susceptibility, fungal spore, and pollen, were analyzed. The results indicate that the AMS 14 C ages of the charcoal range between 5.4 and 5.0 cal. ka BP, consistent with OSL dating from the charcoal layers in the DJCN 3-2-2 section ( 5.5 ka BP). The functional analysis of the stone artifacts and dating results showed that the site was a seasonal, relative long-term, and central camp which was used for processing of stone artifacts, cutting and consuming food and the production of daily necessities. Charcoal, magnetic susceptibility, and fungal spores from the DJCN 3-2-2 section revealed that prehistoric human activities began at 5.8 ka BP and significantly intensified during the period of 5.6–5.5 ka BP and then gradually weakened. Pollen assemblages indicated that the vegetation was dominated by alpine steppe during the period of 5.8–5.0 ka BP, indicative of a relatively warmer and wetter climatic condition during this period. Taken together, we infer that under the impact of the Neolithic culture in lower altitude of upper Yellow River valley and Microlithic culture in the higher altitude inner Plateau, a Neolithic-Zongri culture had emerged in the transitional region between these two cultures during middle Holocene.